Comments on the Two Historical Reprints in Automation of Directory Assistance - Campbell, Ian (Journal of Telecommunications and the Digital Economy, 2025)
This paper is a comment on the background to the two historical papers reproduced in “Automation of Directory Assistance” in this issue. The experience of this author is that, despite a rapid decline in the service quality and mounting operating costs, Telecom was slow to act on automation of the Directory Assistance Service, did not fully exploit the advantages of the automated system, and provided a Directory Assistance Service that was clearly inferior to world’s best practice. Some benchmarking results are provided as evidence.